Effect of Adiantum philippense Extract on Biofilm Formation, Adhesion With Its Antibacterial Activities Against Foodborne Pathogens, and Characterization of Bioactive Metabolites: An in vitro-in silico Approach - Adnan, Mohd; Patel, Mitesh; Deshpande, Sumukh; Alreshidi, Mousa; Siddiqui, Arif Jamal; Reddy, Mandadi Narsimha; Emira, Noumi; De Feo, Vincenzo (Frontiers in Microbiology, 2020)
Adiantum philippense (A. philippense), an ethnomedicinally important fern has become an interesting herb in searching of novel bioactive metabolites, which can also be used as therapeutic agents. Primarily, in this study, A. philippense crude extract was screened for its phytochemical constituent’s, antagonistic potential and its effect on bacterial adhesion and biofilm formation against common food pathogens. Phytochemical profiling of A. philippense was done by using High Resolution-Liquid Chromatography and Mass Spectroscopy (HR-LCMS), followed by antibacterial activity via agar cup/well diffusion, broth microdilution susceptibility methods and growth curve analysis. Antibiofilm potency and efficacy were assessed on developed, formation and texture of biofilms through light microscopy, fluorescent microscopy, scanning electron microscopy and by the assessment of exopolysaccharide production. Correspondingly, checkerboard test was performed to evaluate the combinatorial effect of A. philippense and chloramphenicol. Lastly, molecular docking studies of identified phytochemicals with adhesin proteins of tested food pathogens were assessed, which helps the bacteria in surface attachment, leading to biofilm formation. A. philippense crude extract was found to be active against all tested food pathogens, displaying a rapid time-dependent kinetics of bacterial killing. A. philippense crude extract also impede with the biofilm matrix via reducing the total content of exopolysaccharide and likewise, the microscopic images revealed a great extent of disruption in the architecture of biofilms. A synergy was observed between A. philippense crude extract and chloramphenicol for E. coli, S. aureus and P. aeruginosa, whereas, additive effect was observed for S. flexneri. Various bioactive phytochemicals were categorised from A. philippense crude extract using HR-LCMS. Molecular docking of these identified phytochemicals were interrelated with the active site residues of adhesin proteins, IcsA, Sortase A, OprD, EspA and FimH from S. flexneri, S. aureus, P. aeruginosa and E. coli, respectively. Thus, our findings represents the bioactivity and potency of A. philippense crude extract against food pathogens not only in their planktonic forms but also against/in biofilms for the first time. We have also correlated these findings with the possible mechanism of biofilm inhibition via targeting adhesin proteins which could be explored further to design new bioactive compounds against biofilm producing pathogenic food bacteria’s.